2021
DOI: 10.1016/j.jinf.2020.08.036
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 patients display distinct SARS-CoV-2 specific T-cell responses according to disease severity

Abstract: COVID-19 patients display distinct SARS-CoV-2 specific T-cell responses according to disease severity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 7 publications
5
31
0
Order By: Relevance
“…In our study, the frequencies of SARS‐CoV‐2–specific T cells were in fact in the same range as those observed in convalescent patients from predominantly mild 13,18 or severe COVID‐19 11 . Interestingly, Kroemer et al observed higher numbers of IFNγ‐producing T cells reactive to N peptide pool in patients with mild illness as compared to patients with severe pneumonia, 21 to 53 days following symptoms onset 19 . Such preliminary observations in convalescent individuals suggest that the amplitude of the T cell response may not directly impact disease severity.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, the frequencies of SARS‐CoV‐2–specific T cells were in fact in the same range as those observed in convalescent patients from predominantly mild 13,18 or severe COVID‐19 11 . Interestingly, Kroemer et al observed higher numbers of IFNγ‐producing T cells reactive to N peptide pool in patients with mild illness as compared to patients with severe pneumonia, 21 to 53 days following symptoms onset 19 . Such preliminary observations in convalescent individuals suggest that the amplitude of the T cell response may not directly impact disease severity.…”
Section: Discussionsupporting
confidence: 85%
“…T cells are critical for elimination of SARS-CoV infection. 36,[74][75][76][77][78] Here, hAd5 expressed S and N elicited strong antigen-specific IFN-g, but virtually no IL-4 secretion from T cells of previously infected SARS-CoV-2 patients, pointing to Th1 dominance. Antiviral Th1 cytokine responses eliminate a variety of viruses from infected hosts 79 including the virus closely related to SARS-CoV-2, SARS-CoV.…”
Section: Discussionmentioning
confidence: 89%
“…All patients were enrolled after the signature of informed consent in accordance with the French regulation. Three cohorts of patients were enrolled: i) patients with mild illness COVID-19 infection without cancer, whose clinical parameters have been described elsewhere [ 11 ] ii) patients with solid tumors, iii) patients with hematological malignancies. The analyzed population was diagnosed with COVID-19 between March 10 and May 20.…”
Section: Methodsmentioning
confidence: 99%